Applying of dilatometric effect for resistance welding automation - Bondarenko, O. F.; Dubko, A. H.; Sydorets, V. M.; Bondarenko, Iu. V. (Technology and design in electronic equipment, 2017)
The important issue of resistance spot welding control to obtain high quality welded joints, especially in living tissue welding, is considered. The actual state of the issue is described and analyzed. In order to improve the quality of welded joints, the applying of dilatometric effect to control the resistance spot welding process, namely of shifting the welding electrodes, is suggested. To register the shifting, the use of modern inertial microelectromechanical sensors (MEMS) is proposed. The experimental measuring system, which processes the MEMS-sensor signal and makes it suitable for use as a feedback signal, is developed. The structure and operational algorithm of the system are described. The abilities of measuring with MEMS-sensors the values of electrode shifting caused by dilatometric effect under resistance welding are assessed. This method and equipment are recommended for welding the metals, as well as for welding the living tissues. The results of preliminary studies prove the advisability and relevance of the suggested solutions.